Continuous line bezel correction with rotatable orientation screen in improving collaborative drawing on the multi-mobile system - Ong, Beng Liang (2018)
As a more robust alternative to tabletop system, the multi-mobile system is also benefiting humans’ interaction by combining multiple mobile devices to become shared and larger touch surface display. Although it functions similarly to a tabletop system, several issues arise from the interaction and collaboration of mobile devices’ users in a multi-mobile system which were not found in the interactive tabletop technology:(i) gaps between the screens and bezels issues and (ii) the inverted users’ views caused by the user interface .This research investigates the effects of bezels and screen orientation on a larger shared screen display, and further proposes and implements the solution which is the “Continuous Line Bezel Correction with Rotatable Screen Orientation” that supports on the interaction challenges, particularly in collaborative drawing activities. The user-centered design approach was adopted throughout the research which was based on three key characteristics; including the early focus on users and tasks, empirical measurement and iterative design. Three main studies were carried out with the prototypes by using quantitative and qualitative approaches to understand the underlying issues. Firstly, the preliminary study investigated the impact of bezels and screen orientation on a multi-mobile system in a drawing application such as upside-down orientation, participants’ working position, and disjointed drawing outcomes. The second and third studies measured the performance of the “Continuous Line Bezel Correction with Rotatable Screen Orientation” in solving the bezel and screen orientation issues via the user-based usability tests final two different versions of prototypes. After analyzing the collected data, positive increment on the proposed solutions was found. With the implementation of the continuous spatial configuration, the average time taken for participants to complete the task was improved by 9% and the gaps and disjointed object had improved visually. Moreover, with the implementation of rotational function, the average time taken for participants to complete the task had been shortened by 7.6% and with no inverted object drawn. As a result, the outcomes revealed that the gaps and spaces between mobile screens were found to have been reduced by 94.8%, where the participants remained in a static yet productive position. Hence, these findings implied that the proposed solutions can enrich the users’ experience on the system. In conclusion, the findings of this research contributes to the growing body of research on multi-platform or multi-device system by implementing the proposed solution to further address similar issues in their research works.